Lean supply chain management in garment industry using value stream mapping. (25th August 2020) - Kumar, D. Vasanth; Mohan, G. Madhan; Mohanasundaram, K.M.
Value stream mapping (VSM) is an operative tool in lean manufacturing that supports current state mapping and future state mapping which helps to identify the possible potentialities. It increases the value added activities in production process by eliminating non-value activities and reducing the work-in-process. This paper signifies the implementation of VSM in a garment industry, as a start-up to lean manufacturing. Initially, an analysis with VSM is performed to determine the processes and material flow. It describes the current state for existing position and future state for the proposed development plan, particularly segregating value activities and non-value activities. Based on the outcomes, the fulfilment of value stream implementation are reduction in production time, inventory level and lead time. This implementation of VSM in middle range garment industry shows significant improvements. Hence, the understanding of this implementation is essential to adapt in similar garment industries to identify improvements in small and medium scale industries.